2021
DOI: 10.3389/fped.2021.734184
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of the Physical Health of the Adolescent Brain Cognitive Development Study Cohort at Baseline

Abstract: Physical health in childhood is crucial for neurobiological as well as overall development, and can shape long-term outcomes into adulthood. The landmark, longitudinal Adolescent Brain Cognitive Development StudySM (ABCD study®), was designed to investigate brain development and health in almost 12,000 youth who were recruited when they were 9–10 years old and will be followed through adolescence and early adulthood. The overall goal of this paper is to provide descriptive analyses of physical health measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Yearly height (nearest 0.1inch) and weight (nearest 0.1lb) assessments (measured twice, a third was collected in cases of large discrepancy) were gathered by a trained researcher. The closest two measurements were averaged and converted into BMI (kg/m 2 ) and BMI percentiles according to the CDC’s sex-age-height-weight specific growth charts (Kuczmarski et al, 2002) for clinical interpretations, only as they are prone to several biases (Hendrickson & Pitt, 2021; Palmer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Yearly height (nearest 0.1inch) and weight (nearest 0.1lb) assessments (measured twice, a third was collected in cases of large discrepancy) were gathered by a trained researcher. The closest two measurements were averaged and converted into BMI (kg/m 2 ) and BMI percentiles according to the CDC’s sex-age-height-weight specific growth charts (Kuczmarski et al, 2002) for clinical interpretations, only as they are prone to several biases (Hendrickson & Pitt, 2021; Palmer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of delays in milestone attainment in our study using the ABCD study is lower than the national estimates of development delays when applying the CDC guidelines on milestone attainment [ 58 ]. This might partly reflect errors in maternal recall or that the ABCD study has excluded children with several major neurological disorders, extreme birth outcomes, or birth complications that resulted in hospitalization for more than 1 month in the baseline enrollment [ 14 , 15 ]. Our study shows that a delay in milestone attainment, even when using subclinical cutoff values in a sample of children without several major neurological disorders, is predictive of childhood cognitive and behavioral functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The public-school recruitment approach and a stratified probability sampling strategy were utilized to capture the sociodemographic diversity of the US population. Children with following conditions were excluded from the ABCD study at baseline recruitment (details may be found in ABCD release note 1.0): child not fluent in English; MRI contraindication (e.g., irremovable ferromagnetic implants or dental appliances, claustrophobia); gestational age < 28 weeks or birth weight < 1200 g; birth complications that resulted in hospitalization for more than 1 month; current diagnosis of schizophrenia, autism spectrum disorder, mental retardation/intellectual disability; or known alcohol/substance use disorder [ 14 , 15 ]. For the current study, we focus on 5360 singleton children with a baseline parental questionnaire completed by their biological mothers that included information on early-life developmental milestones.…”
Section: Methodsmentioning
confidence: 99%
“…The closest two measurements were averaged and converted into BMI (kg/m 2 ) and BMI percentiles according to the CDC's sex-age-height-weight specific growth charts ( 36 ). Given the biases surrounding z-score and percentiles ( 38 , 39 ), these are provided only for clinical interpretations while BMI was used in the statistical analyses.…”
Section: Methodsmentioning
confidence: 99%